Repair with annuloplasty only of balanced bileaflet mitral valve prolapse with severe regurgitation. (23rd December 2021) - Raanani, Ehud; Schwammenthal, Ehud; Moshkovitz, Yaron; Cohen, Hillit; Kogan, Alexander; Peled, Yael; Sternik, Leonid; Ram, Eilon
Abstract: OBJECTIVES: Repair of severe mitral valve and mitral regurgitation (MR) in patients with degenerative bileaflet pathology can be challenging. Initial results with a ring-only repair (ROR) approach have shown promising results, but long-term outcomes in larger series are lacking. We report on outcomes of ROR in severe MR secondary to bileaflet prolapse, including Barlow's disease. METHODS: Eighty patients with degenerative multi-segment bileaflet disease underwent ROR for severe MR with a predominantly central regurgitant jet indicating balanced bileaflet prolapse. The main outcome measure of this study was long-term recurrent MR probability. Secondary outcomes were late mortality, reoperation and in-hospital complications. RESULTS: The mean age was 53 ± 15 years and 54% were males. The mean ejection fraction was 59.2 ± 6.6, 24% and 40% had atrial fibrillation. Barlow's disease was found in 77% of the patients. Minimally invasive surgery was performed in 15 patients (19%). There were no perioperative mortalities or cerebrovascular events in the entire cohort. Post-repair mild outflow tract obstruction (systolic anterior motion) was observed in 4 patients (5%) after ROR. In a mean follow-up of 60 ± 48 months, there was 1 case of death. At follow-up, there was 1 (1%) reoperation due to recurrent MR, and 4 patients who had recurrent moderate or more MR. The 10-year freedom from recurrent MR was 97%. None had severe MR at the latest follow-up. CONCLUSIONS: In patients with severe MR and a central regurgitant jet secondary to balanced multi-segment bileaflet mitral valve prolapse, ROR is a simple and efficient approach providing excellent long-term results without a substantial risk of systolic anterior motion. Abstract : Repair is considered preferable over replacement in the treatment of degenerative mitral valve (MV) disease with severe mitral regurgitation (MR) [1–5] but can be particularly challenging in Barlow's disease, the most advanced form of myxomatous degeneration, which is characterized by excessive multi-segment tissue proliferation and marked annular dilatation [6–8].